Toward single motor driven biped robot - Li, Mingjian (2008)
This thesis investigated the detailed properties of both SMD and EA. Their combination and application in biped robots are demonstrated as well. An experimental Purposeful Elastic Joint (PEJ) robot based on the SMD and EA concept has been designed and fabricated. The mathematical model of the PEJ is developed. Experimental and simulation results are compared. Based on the theory of variable structure systems and nonlinear PWM control, a local controller is designed and tested on the PEJ. In the modeling and simulation of SMD biped robot walking, an effective gait planning method is developed to generate the stable walking gait only based upon several simple walking parameters. The local controllers and gait planning algorithm are integrated and tested with an SMD biped robot in ADAMS. The experimental and simulation results show that the combined actuation approach of Advanced SMD for biped robot is viable and promising. With brief discussion on future work of SMD biped robot, the thesis predicts that real walking SMD biped robot will come to world soon.